Kebijakan Redasional Majalah Gadis dalam Membuat Konten Digital - Past Novel (Universitas Multimedia Nusantara, 2016)
ass media evolves along with the technological advancement, in which the internet enables better access of information, both the reception and the distribution of information. Magazine is one of the mass media that also benefitted from the technology development and internet connection, as it can produce online or digital version. The internet offers easier access to mass media, interactivity, and reduction in the cost of production and distribution. However, there are also some risks and side effects of the popularity of online mass media. GADIS magazine, founded 35 years ago, also publishes digital or online version. This research analyzes the digital content of GADIS magazine and interviewed the editors of the magazine. From the point of view of the editorial department, this research analyzes the steps and considerations of the magazine in publishing its digital content. The result is expected to reveal the views of the magazine's editorial department in anticipating and responding to the risk of technological use, mainly for the digital or online magazine. Keywords: mass media, magazine, online, digital media